2017
DOI: 10.1109/twc.2016.2633522
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Resource Allocation for Mobile-Edge Computation Offloading

Abstract: Mobile-edge computation offloading (MECO) offloads intensive mobile computation to clouds located at the edges of cellular networks. Thereby, MECO is envisioned as a promising technique for prolonging the battery lives and enhancing the computation capacities of mobiles. In this paper, we study resource allocation for a multiuser MECO system based on time-division multiple access (TDMA) and orthogonal frequency-division multiple access (OFDMA). First, for the TDMA MECO system with infinite or finite cloud comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
819
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,421 publications
(821 citation statements)
references
References 30 publications
1
819
0
1
Order By: Relevance
“…x i = 1 if MU i is allocated the resource, and x i = 0 otherwise. Now, (10) and (11) are the constraints of the fill area ( Figure 3C). The others are the same as IP1.…”
Section: A Performance-bound Algorithm Based On Variable Relaxationmentioning
confidence: 99%
See 2 more Smart Citations
“…x i = 1 if MU i is allocated the resource, and x i = 0 otherwise. Now, (10) and (11) are the constraints of the fill area ( Figure 3C). The others are the same as IP1.…”
Section: A Performance-bound Algorithm Based On Variable Relaxationmentioning
confidence: 99%
“…Till now, lots of work have been carried out for the resources allocation problem of the MEC system. At first, the offloading decision and resources allocation depend on the properties of the task, ie, binary offloadable task or partial offloadable task . For the former, the tasks are either locally implemented or offloaded to the cloud to execute, while for the latter, a task can be segmented into at least two parts, and one of them is performed at local device, and the other is offloaded to the cloud platform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changsheng You et al [30] suggested a resource allotment aimed at a multiuser MECO framework based on time-division multiple access (TDMA) accompanied by orthogonal frequency-division multiple access (OFDMA). To begin with, the ideal resource allocation intended for the TDMA MECO framework with infinite or finite cloud computation capacity was framed as a convex optimization issue for reducing the weighted totality mobile energy consumption under the limitation of computation latency.…”
Section: Related Workmentioning
confidence: 99%
“…The development of 3C solutions has a long history behind, as it comes from conventional cloud computing [16], through fog structures [17], all the way to the network edge [18,19]. This transition, in turn, underpins a new concept of mobile edge computing (MEC) as an emerging computing and caching paradigm [20].…”
Section: Introductionmentioning
confidence: 99%